2020
DOI: 10.1007/s13577-020-00387-x
|View full text |Cite
|
Sign up to set email alerts
|

HDAC inhibitors promote pancreatic stellate cell apoptosis and relieve pancreatic fibrosis by upregulating miR-15/16 in chronic pancreatitis

Abstract: In chronic pancreatitis, PSCs are activated by proinflammatory cytokines to induce pancreatic fibrogenesis. HDAC inhibition protected against the pancreatic fibrosis and the apoptosis of PSCs through induced apoptosis and depressed inflammation. In our study, we found that miR-15 and miR-16 decreased significantly in chronic pancreatitis and HDAC inhibition could recover the levels of these two miRNAs. HDAC regulated the transcription of miR-15 and miR-16, which then modulate the apoptosis and fibrosis of PSCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Smad7 is an inhibitory protein of the TGF-β/Smad signaling pathway that can effectively inhibit the phosphorylation of signal activators (Smad2 and Smad3) and subsequent downstream signal activation [20]. However, other studies have shown that miR-16 can significantly inhibit the expression of smad2 [21], smad3 [22], and smad5 [23] in fibroblasts, as well as the phenotypic remodeling process of fibroblasts to myofibroblasts induced by TGF-β in many ways, thus playing an anti-fibrotic role.…”
Section: Regulation Of Cell Transformationmentioning
confidence: 99%
“…Smad7 is an inhibitory protein of the TGF-β/Smad signaling pathway that can effectively inhibit the phosphorylation of signal activators (Smad2 and Smad3) and subsequent downstream signal activation [20]. However, other studies have shown that miR-16 can significantly inhibit the expression of smad2 [21], smad3 [22], and smad5 [23] in fibroblasts, as well as the phenotypic remodeling process of fibroblasts to myofibroblasts induced by TGF-β in many ways, thus playing an anti-fibrotic role.…”
Section: Regulation Of Cell Transformationmentioning
confidence: 99%
“…Overexpression of miR-15b or miR-16 in activated PSCs originating from rats resulted in the reduction of BCL-2 mRNA and an increase of apoptosis as shown by increased RNA and protein levels of caspase 3, 8, and 9 [ 110 ]. In vivo studies in rats showed that treatment with HDAC inhibitors (Vorinostat and Trichostatin A) alleviates the fibroinflammatory phenotype of CP as demonstrated by reduced serum levels of IL-6 and TNFα and reduced levels of markers of activated PSCs such as GFAP and α-SMA [ 109 ]. Simultaneously, Vorinostat treatment increased miR-15/miR-16 and induced apoptosis of PSCs.…”
Section: Chronic Pancreatitismentioning
confidence: 99%
“…Simultaneously, Vorinostat treatment increased miR-15/miR-16 and induced apoptosis of PSCs. Overexpression of miR-15/miR-16 decreased SMAD5, TGFβ pathway effector, and BCL-2 [ 109 ] ( Figure 5 ).…”
Section: Chronic Pancreatitismentioning
confidence: 99%
“…In addition, miR-31 promotes epithelial regeneration via the Wnt and Hippo signaling pathways [ 66 ]. In chronic pancreatitis, upregulated miR-15 and miR-16 expression can alleviate apoptosis and fibrosis by targeting both BCL-2 and SMAD5 [ 67 ].…”
Section: The Role Of Mirnas In Ccamentioning
confidence: 99%